2013
DOI: 10.1021/pr400900j
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of Missing Proteins Provides Clues to Help Define All of the Protein-Coding Genes on Human Chromosome 1

Abstract: Our first proteomic exploration of human chromosome 1 began in 2012 (CCPD 1.0), and the genome-wide characterization of the human proteome through public resources revealed that 32-39% of proteins on chromosome 1 remain unidentified. To characterize all of the missing proteins, we applied an OMICS-integrated analysis of three human liver cell lines (Hep3B, MHCC97H, and HCCLM3) using mRNA and ribosome nascent-chain complex-bound mRNA deep sequencing and proteome profiling, contributing mass spectrometric eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 40 publications
0
29
0
1
Order By: Relevance
“…In 2014, the Chinese Human Proteome Project completed the multi-omics level analysis of liver cancer cell lines [51]. From each cell line, more than 14,000 translating genes were detected and only 2/3 of the protein products were detected in MS, showing the high sensitivity of RNC-seq [22,51,132,133,134].…”
Section: Application Of Translatomicsmentioning
confidence: 99%
“…In 2014, the Chinese Human Proteome Project completed the multi-omics level analysis of liver cancer cell lines [51]. From each cell line, more than 14,000 translating genes were detected and only 2/3 of the protein products were detected in MS, showing the high sensitivity of RNC-seq [22,51,132,133,134].…”
Section: Application Of Translatomicsmentioning
confidence: 99%
“…In a recent effort to characterize all the missing proteins, an integrative OMICS approach was employed, combining MS-based proteomics, RNAseq and ribosome profiling, an emerging technique that identifies the translation potential of mRNAs present in a sample (120). This approach, utilising proteome, transcriptome and translatome data, reduced the as yet uncharacterised genes to ~15%, most of which are predicted to be tissue-specific.…”
Section: Combining Omics Approaches To Maximise Functionmentioning
confidence: 99%
“…6 Some missing proteins are also likely to be expressed only under certain stimulus or stress. 5 Recently, some mass spectrometry (MS) evidences were reported evidences to identify missing proteins from human brain tissues, 7 lung tissues and cell lines, 8 colorectal cancer samples, 9 and hepatocellular carcinoma samples 10 , showing the significance of clinical samples in detecting missing proteins. In addition, the distinct proteome profiles deciphered by the draft map of the human proteome 1 also revealed that missing proteins may even be expressed only during development in embryo or fetal tissues, with over 700 proteins having ten-fold increase in expression level compared to the adult counterparts.…”
Section: Introductionmentioning
confidence: 99%